INFRARED SPECTROSCOPIC INVESTIGATIONS ON THE REACTION PRODUCTS RESULTED FROM THE INTERACTION BETWEEN SILVER(I) SALTS WITH UREA AT 90 OC: Life Science-Bioinorganic Chemistry - SALMAN, MAHMOUD (International Journal of Life Science and Pharma Research, 2012)
The ligational behavior of urea (U) with silver(I) salts like silver(I) chloride, silver(I) sulfate, silver(I) acetate, silver(I) nitrate, and silver(I) iodide at 90 oC temperature with 4-6 hrs has been studied by conductivity measurements, infrared spectra, scanning electron microscopy (SEM), Energy-dispersive X-ray spectroscopy (EDX), and x-ray powder diffraction (XRD). The high values of molar conductivity of the resulting urea complexes show them to be electrolytes in nature. The physical and spectral data were well explained in terms of the formation of [Ag2(U)(NCO)]Cl.xH2O, [Ag2(U)(NCO)].½SO4.xH2O, [Ag2(U)(NCO)]CH3COO.xH2O, [Ag2(U)(NCO)]NO3 .xH2O, and [Ag2(U)(NCO)]I.xH2O, On the basis of the infrared spectral data and the values of stretching vibrational bands of both –C=O and –NH2 groups, the complexation of metal ions toward urea was distinguished.